Měření humeroulnární inkongruity loketního kloubu u psů pomocí výpočetní tomografie - Snášil, R; Proks, P; Nečasová, A; Michalčáková, K; Nečas, A (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2017)
PURPOSE OF THE STUDY The purpose of the study is to compare the repeatability and reproducibility of quantitative and subjective evaluation of elbow humeroulnar incongruity (HUI) using computed tomography (CT) on an in vivo canine model. MATERIAL AND METHODS HUI was evaluated on canine (n = 50) elbow joints (n = 100). The computed tomography of elbow joints was performed under intravenous sedation. Multiplanar reconstructions (MPR) were produced. HUI was evaluated on sagittal MPR images subjectively and by measuring the subluxation index (SI). The SI was defined by measuring the distance between the centres of two circles, the shape of which corresponded the most with the shape of the trochlear notch of the ulna at sagittal crest and the shape of humeral trochlea. This distance was divided by the radius of the circle (r) defining the humeral trochlea. HUI was subjectively evaluated based on the width of the joint space at the greatest caudal convexity of the trochlear notch of the ulna. Three categories of HUI were established: 0 (congruent), 1 (moderately incongruent), 2 (strongly incongruent). Measurement and evaluation of HUI was conducted by two evaluators twice at a one-month interval between the first and second measurement. The statistical analysis was carried out using the repeated measures ANOVA and the Cohen s kappa coefficient. RESULTS The mean SI was 11.14 (SD 8.703). The SI values measured by two evaluators were statistically significantly different (p < 0.05). Contrarily, there was no statistically significant difference between the two measurements of the same evaluator (p > 0.05). The subjective evaluation of HUI done by two evaluators showed a mean to substantial agreement (Kappa = 0.53-0.79). There was a substantial to almost perfect agreement between the results of two evaluations carried out by a single evaluator (Kappa = 0.79-0.83). DISCUSSION The radiographic detection of moderate incongruity is unreliable, especially on account of wrongly positioned elbow joint, superposition of bone structures and due to the evaluation of three-dimensional bone structure through a two-dimensional image. Evaluation of humeroulnar congruity by computed tomography (CT) enables to assess the congruity of joints without the superposition of neighbouring bone structures. The quantification of humeroulnar incongruity using the SI does not show a higher degree of agreement between two evaluators as against the subjective evaluation of HUI. On the contrary, the agreement between two measurements of a single evaluator was high in both the cases. CONCLUSIONS Dog is a suitable model animal for evaluation of HUI of elbow joints due to frequent incidence of elbow dysplasia associated with HUI. The quantification of HUI at the expense of subjective evaluation of HUI is often overrated in radiological studies. Key words: dog, elbow, humeroulnar incongruity.
Keywords: Animals; Humerus; Tomography, X-Ray Computed; nemoci psů; Ulna; Dog Diseases; Joint Diseases; Dogs; nemoci kloubů; stupeň závažnosti nemoci; humerus; odchylka pozorovatele; Observer Variation; zvířata; Severity of Illness Index; psi; přední končetina; ulna; Forelimb; počítačová rentgenová tomografie